Effect of Yoga on Cardiovascular Autonomic Reactivity in Essential Hypertensive Patients - Khadka, R; Paudel, BH; Sharma, VP; Kumar, S; Bhattacharya, N (Health Renaissance, 2011)
Background and objective: We aimed to investigate the effect of yoga on cardiovascular autonomic reactivity in essential hypertensive patients. Methods: The study was conducted on 14 essential hypertensive patients, who were on salt-reduction and similar antihypertensive drugs. They were randomized into two groups; control (n=7; age 42.2±11.9 years) and yoga (n=7; age 44.9±10.8 years). The yoga group practiced yoga for ½ h/d, 6 d/ week for 6 weeks. The control group did not practice any type of yogic exercises or relaxation techniques. Autonomic function tests consisting of deep breathing, Valsalva maneuver, handgrip (HGT), and head-up tilt (HUT) tests of all patients were assessed at 0 week and every two weeks for 6 weeks. The data were analyzed using Friedman test followed by multiple comparisons. Results: In yoga group significant reduction in resting heart rate, SBP, and DBP were found after 4 weeks of yogic practices as compared to baseline recording; HR [84(78-94.5) Vs 72(67.5-77); p=0.028], SBP[144(140-165) Vs 130(125- 144); p=0.018], and DBP[98(94-101) Vs 88(78-90); p=0.018]. Similarly, significant reduction in SBP was found after yogic practices in response to HGT and HUT although the magnitude of changes was increased or comparable to control. There was significant increase in Valsalva ratio after yogic practices [1.17(1.12-1.4) Vs 1.33(1.29-1.55); p=0.018]. Conculsion: Yoga combined with anti-hypertensive drugs is effective in reducing BP in resting condition and increasing parasympathetic reactivity. It is also found to normalize cardiovascular autonomic function in hypertensive patients. Keywords: Yoga; essential hypertension. DOI: 10.3126/hren.v8i2.4421 Health Renaissance, May-Aug 2010; Vol 8 (No.2):102-109